Analysis Of Online Health Education Method Through Android On Teenages 'Knowledge And Care Related To Tuberculosis Prevention In SMP Negeri 1 Prambon, Nganjuk District - Noviani, Hesti Eka; Muhammad Ali Sodik (Universitas STRADA Indonesia, 2020)
Tuberculosis is categorized into the category of infectious diseases caused by the bacterium Mycobacterium Tuberculosis. Based on research data, the prevalence of tuberculosis cases in Nganjuk Regency is 35%, while the target is 0%, indicating that Nganjuk Regency has experienced an increase in the number of tuberculosis sufferers. Based on previous research, 7 out of 10 children do not know about Tuberculosis.Health promotion strategies are needed to increase knowledge and awareness of adolescents about the prevention of tuberculosis, therefore Health Education techniques are applied. The purpose of this study was to determine the differences and effects of participating in health education on knowledge and concern for tuberculosis prevention. The research design used analytic observational with a case control approach. The research was conducted at SMP Negeri 1 Prambon. The sample amounted to 166 people. Data collection was carried out by means of a questionnaire. Bivariate analysis used the Man - Whitney test. The study found that there was a difference in the mean of knowledge and concern in TB prevention between adolescents who participated and those who did not participate in the Health Education program (p-value 0,000). The effect of health education participation on knowledge is 75% p value - value = 0.000. The effect of Health Education participation on caring is 74% p value - value = 0.000. Health promotion methods using Health Education have succeeded in increasing adolescent knowledge and awareness about the prevention of Tuberculosis and influencing the knowledge and awareness of adolescents in carrying out Tuberculosis prevention